2019
DOI: 10.1021/acs.jpcc.9b05068
|View full text |Cite
|
Sign up to set email alerts
|

Heat-, Load-, and Shear-Driven Reactions of Di-tert-butyl Disulfide on Fe(100)

Abstract: The surfaces of lubricated mechanical components operating under extreme conditions are protected by films that form in the presence of additives in lubricant formulations. Film formation is believed to be accelerated by heat, load, and shear force in the sliding interface, but the individual contributions of these factors are poorly understood. In this study, we use reactive molecular dynamics simulations to deconvolute the effects of heat, load, and shear force on chemical reactions between di-tert-butyl dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Simulations of sliding across a range of temperatures showed that shear accelerates the reaction and increases the reaction yield [83] The reaction yield was quantified by the rate-limiting step, and the simulations demonstrated that the energy barrier was lowered by shear force acting along the reaction coordinate for the rate limiting step of the reaction. Next, the reaction yield at each temperature was fit to the Bell model [25], Equation 1, rewritten as [83]:…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 96%
See 2 more Smart Citations
“…Simulations of sliding across a range of temperatures showed that shear accelerates the reaction and increases the reaction yield [83] The reaction yield was quantified by the rate-limiting step, and the simulations demonstrated that the energy barrier was lowered by shear force acting along the reaction coordinate for the rate limiting step of the reaction. Next, the reaction yield at each temperature was fit to the Bell model [25], Equation 1, rewritten as [83]:…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 96%
“…The reaction pathway was identified as dissociation of the di-tert-butyl disulfide (S-S bond breaking), chemisorption of tert-butyl sulfide (Fe-S bond formation), and then, tert-butyl radical release (S-C bond breaking), as illustrated in Figure 5a-c, where the radical release was found to be the rate-limiting step [51]. Simulations of sliding across a range of temperatures showed that shear accelerates the reaction and increases the reaction yield [83] The reaction yield was quantified by the rate-limiting step, and the simulations demonstrated that the energy barrier was lowered by shear force acting along the reaction coordinate for the rate limiting step of the reaction. Next, the reaction yield at each temperature was fit to the Bell model [25], Equation 1, rewritten as [83]:…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…28 Indeed, NEMD simulations have recently been performed for a wide range of other systems using ReaxFF. [99][100][101] It will also be useful to validate the results of the ReaxFF NEMD simulations against AIMD simulations. For example,…”
Section: Simulationsmentioning
confidence: 99%
“…28 For example, NEMD simulations have recently been used to study the tribopolymerization of aldehydes between alumina surfaces, 29 phosphoric acid, 30,31 allyl alcohols, 32 and terpenes 33 between sliding silica surfaces, and cyclopropane carboxylic acid between iron oxide surfaces. 34 They have also been used to study the mechanochemical decomposition of alkyl sulfides between sliding iron surfaces 35 and perfluoropolyethers (PFPEs) between DLC surfaces, 36 the vapour phase lubrication of trialkylphosphates 37 and trialkylphosphites 38,39 between iron surfaces, and the ultralow friction of organic friction modifier additives between DLC surfaces. 40 Most of these NEMD simulations employed many-body empirical force fields, [30][31][32][33][34][35][36] while others use first principles methods, 29,[37][38][39] or sometimes a combination of both of these techniques.…”
Section: Introductionmentioning
confidence: 99%